Towards spaceborne monitoring of localized CO2 emissions: an instrument concept and first performance assessment - Strandgren, Johan; Krutz, David; Wilzewski, Jonas S.; Paproth, Carsten; Sebastian, Ilse; Gurney, Kevin; Liang, Jianming; Roiger, Anke; Butz, André (Atmospheric measurement techniques, 2020)
The UNFCCC (United Nations Framework Convention on Climate Change) requires the nations of the world to report their carbon dioxide (CO2) emissions. The independent veriﬁcation of these reported emissions is a cornerstone for advancing towards the emission accounting and reduction measures agreed upon in the Paris Agreement. In this paper, we present the concept and ﬁrst performance assessment of a compact spaceborne imaging spectrometer with a spatial resolution of 50 × 50 m2 that could contribute to the “monitoring, veriﬁcation and reporting” (MVR) of CO2 emissions worldwide. CO2 emissions from medium-sized power plants (1-10 Mt CO2 yr−1), currently not targeted by other spaceborne missions, represent a signiﬁcant part of the global CO2 emission budget. In this paper we show that the proposed instrument concept is able to resolve emission plumes from such localized sources as a ﬁrst step towards corresponding CO2 ﬂux estimates.
Im Titel ist "2" tiefgestellt
Gesehen am 12.10.2020